Business Incubators in Asian Developing Countries - Jamil, Farhan; Ismail, Kamariah; Siddique, Muhammad; Khan, Muhammad Muddassar; Kazi, Abdul Ghafoor; Qureshi, Muhammd Imran (International Review of Management and Marketing, 2016)
The purpose of this study is to review the literature of business incubators particularly in developing countries context. The extensive literature in developing countries like China, India, Malaysia and Pakistan supports the concept of business incubators as a part of their national innovation system and also for economic development. We further found from the literature that business incubators contribute in achieving the commercialization targets, creating new startups, promoting the entrepreneurial culture, innovation and generating revenue. However, the concept is at initial stages of implementation particularly in Pakistan and Malaysia. The lack of human and technical expertise and financial constraints are the main reasons behind this slow progress. This study contributes to improve the understanding of business incubator’s strategies, objectives, functionalities, implementation and outcome in developing countries. Additionally, this study provides the useful information to policy makers, government, academicians and practitioners about the business incubators. Keywords: business incubators, technical expertise, financial constraints JEL Classifications: J10, M10